2010
DOI: 10.1128/jb.00725-10
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis rnjB Is Required for Pilin Gene Expression and Biofilm Formation

Abstract: Pili in Gram-positive bacteria play a major role in the colonization of host tissue and in the development of biofilms. They are promising candidates for vaccines or drug targets since they are highly immunogenic and share common structural and functional features among various Gram-positive pathogens. Numerous publications have helped build a detailed understanding of pilus surface assembly, yet regulation of pilin gene expression has not been well defined. Utilizing a monoclonal antibody developed against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…Our library screen method once again (8,10) proved to be of great value in studying genetic determinants involved in bacterial surface protein expression, since it can detect changes that occur at any level from transcription to surface anchoring. Since Ace mRNA levels are not affected by deletion of ccpA, the link between these two factors would not have been discovered through traditional genetic or transcriptome analysis.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…Our library screen method once again (8,10) proved to be of great value in studying genetic determinants involved in bacterial surface protein expression, since it can detect changes that occur at any level from transcription to surface anchoring. Since Ace mRNA levels are not affected by deletion of ccpA, the link between these two factors would not have been discovered through traditional genetic or transcriptome analysis.…”
Section: Figmentioning
confidence: 99%
“…The whole-cell ELISA screen was performed as previously described (10), with some modifications. The Tn library of cells was cultured for 24 h before being diluted 1:10 into new wells containing BHI medium and subsequently cultured at 37°C for 1.5 h. Anti-Ace monoclonal antibody (MAb) 70 at 2 g/ml was used to label cells, followed by the addition of 100 l of a 1:3,000 dilution of goat anti-mouse IgG-horseradish peroxidase (HRP) (Jackson ImmunoResearch).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilusspecific class C sortase (Bps, for biofilm-and pilusassociated sortase), catalyses the assembly of the structural subunits into pili, before the housekeeping sortase A (SrtA) covalently binds the elongated pili to the cell wall via EbpB (Nallapareddy et al, 2006;Sillanpää et al, 2013). Studies on ebp regulation identified the upstream ebpR gene (Bourgogne et al, 2007) and the rnjB gene (Gao et al, 2010) as activators at the mRNA level, while the Fsr quorum-sensing system was described as a weak repressor (Bourgogne et al, 2006). In addition, a recent report by Montealegre et al (2015) demonstrated that E. faecalis uses the rare initiation codon ATT, found in all E. faecalis strains sequenced, as the start codon of the tip pilin EbpA and that this start codon results in reduced expression, at the translational level, relative to an engineered ATG, and negatively affects Ebp-associated functions (Montealegre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%